Effect of Lateral Positioning on Oxygen Levels in an Obese, Critically Hypoxic COVID-19 Patient - Sanjith Saseedharan; Shalaka Patil; Gauri Kene; Ashish Yadav; Rujuta Bagade (MAMC Journal of Medical Sciences, 2022)
Abstract COVID-19 is an infectious disease caused by SARS-CoV-2 virus. COVID-19 patients can develop a severe disease that can lead to hypoxic respiratory failure and acute respiratory distress syndrome (ARDS), which requires mechanical ventilation, prone ventilation, and salvage therapy like extracorporeal membrane oxygenation. The COVID lung is a hypoxic lung with myriad of reasons of hypoxia including poor ventilation perfusion mismatch and atelectasis. We present a case report of a morbidly obese individual managed with lateral positioning as a salvage for deteriorating PaO2/FiO2 ratio. We also demonstrated that the improvement of oxygenation was due to the recruitment of previously nonventilated lung areas as demonstrated by electrical impedance tomography (EIT). Our patient was morbidly obese and there was a dearth of man power to perform the prone position on this patient. Moreover, the sheer weight of this patient prevented us from trying the prone position. Hence, this patient was placed in a cycle of left lateral, right lateral, and supine position for 120 minutes each for the subsequent 24 hours. Significant improvement in oxygenation and ventilation was noticed in the EIT and SpO2 measurements. The EIT reading indicated ventilation redistribution to previously collapsed areas of the lung and this change persisted even when the patient was turned supine due the application of positive end expiratory pressure (PEEP) to maintain positive expiratory transpulmonary pressure. These results provide evidence of effectiveness of a lateral positioning in the improvement of oxygenation in COVID-19 ARDS.